(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
The purpose of this research is a scientific ground of forming features financially resource providing of realization of mechanisms of development of enterprise. Taking into account a certain goal such tasks are in-process put and decided: certainly conceptual features of functioning of enterprise, his place and role is rotined in the system of development of regional economy; priority directions of internal market of region development and mechanisms of regulator policy of their providing are set. In basis of methodology and theoretical basis of this research the fixed theories of the economy growing, institucionalizmu, transitional economic systems. Recommendations from the improvement of macroeconomic terms of realization of mechanisms of development of enterprise can be used the organs of central and regional power in the context of development and realization of strategy of socio-economic development regions; in the process of realization of the system of measures on activation of development of enterprise. Complex combination and application of all instruments and forming facilities financially resource, providing of development of enterprises at the internal market is called in the proper measure to support and stimulate all its subjects to realization of measures of forming of their high-quality and structurally balanced development in the Zakarpattya area. The scientific novelty of the got results consists in a ground teoretiko-methodical approaches and applied recommendations in relation to forming financially resource providing of realization of mechanisms of development of enterprise. It is expedient to examine two scenarios of development enterprises, in accordance with which both different composition, volumes, and structure of it, can be formed financially resource providing. First – inertia. Second – innovative and more perspective, however needs complex approach to forming financially resource providing with the extended budgetary investing, preparation, to realization of perspective financially investment projects for business, bringing in of investments of population, active publicly psychological by support.